The Multistage Homotopy Perturbation Method for Solving Chaotic and Hyperchaotic Lü System - M. S. H. Chowdhury; Nur Isnida Razali; Waqar Asrar; M. M. Rahman (Abstract and Applied Analysis)
The multistage homotopy-perturbation method (MHPM) is applied to the nonlinear chaotic and hyperchaotic Lü systems. MHPM is a technique adapted from the standard homotopy-perturbation method (HPM) where the HPM is treated as an algorithm in a sequence of time intervals. To ensure the precision of the technique applied in this work, the results are compared with a fourth-order Runge-Kutta method and the standard HPM. The results show that the MHPM is an efficient and powerful technique in solving both chaotic and hyperchaotic systems.